RECONSTRUCTING SEA-LEVEL CHANGE FROM THE INTERNAL ARCHITECTURE OF STROMATOLITE REEFS: AN EXAMPLE FROM THE MESOPROTEROZOIC SULKY FORMATION, DISMAL LAKES GROUP, ARCTIC CANADA - Kah L.C.; Bartley J.K.; Frank T.D.; Lyons T.W. (My University, 2006)
The Mesoproterozoic Dismal Lakes Group, arctic Canada, contains a relatively thin, yet regionally extensive stromatolitic reef complex that developed subtidally during a major transgression, shoaled to sea level, and was overlain by intertidal to supratidal carbonate and evaporite strata. The September Lake reef complex exhibits a complex internal architecture that records the interaction between stromatolite growth and changes in accommodation space derived from both higher order (4th- or 5th-order, parasequence-scale) changes in sea level and the variable bathymetry of the sea floor. Reef growth, which was initiated during three sea-level cycles, records progressive marine transgression over depositional lows that were formed during pre-reef subaerial exposure and erosion of the underlying strata. A fourth sea-level cycle, represented by spectacular coniform stromatolites with >10 m of synoptic relief, marks a more dramatic rise in sea level and establishment of the main reef complex. Aggradation and eventual shoaling of the reef complex occurred over an additional six sea-level cycles. Only basinward regions of the September Lake reef complex preserve vertical stacking of reefal packages in response to sea-level fluctuations. In contrast, in the main reef core, sea-level fluctuations resulted in subaerial exposure of the reef top, variable karst development, and the progressive infilling of reef topography by progradational reef elements. Assessment of stromatolite growth patterns reveals the complex nature of the reef architecture and permits the determination of higher order changes in relative sea level that were responsible for reef development. © 2006 NRC Canada.
Keywords: Докембрий::Протерозой::Мезопротерозойская; Precambrian::Proterozoic::Mesoproterozoic